(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2023)
The text presents Móin-Móin - Magazine of Studies in the Arts of Puppetry 27th edition, with has the theme “Preservation and conservation of collections in the Puppetry”, showing the main questions that induces the authors and presents a synthesis of the published articles. esta foi a tradução do Guilherme...Leticia precisa revisar